Disemination of Tematic Learning Model Based on Asmaul Husna in Improving Early Childhood’s Religious Values at Ibnu Sina Kindergarten - Ismah, Ismah; Herwina, Herwina (Universitas Negeri Semarang, 2018)
The aim of this research is to disseminate and socialize thematic teaching model based on Asmaul Husna to improve the early childhood’s religious values. The research was conducted in Ibnu Sina kindergarten located in Pondok Cabe Ilir, Pamulang, South Tangerang. Objects of early childhood research in kindergarten Ibn Sina group A and B as well as play groups, with the number of children 21 students. This research is a result of model trial development in 2015 through classroom action research at Lab School Kindergarten, Faculty of Education Science, Muhammadiyah University of Jakarta. Classroom action research was conducted in three cycles, with the result of increasing the religious values ​​of children exceeding 80% based on 19 indicators of religious values ​​that must be owned by the child. The dissemination consists of 5 stages: (1) explaining the concept, (2) demonstrating the model, (3) training the teachers, (4) peer teaching, (5) real teaching (practice) has been done by 3 teachers at Ibnu Sina kindergarten. The results obtained from the dissemination of the model of thematic teaching based on Asmaul Husna is effective in improving the religious values ​​of early childhood. The model has been developed to provide a fun atmosphere for early childhood, because using real media that are in the school environment, the media used is very easy to obtain so as not to complicate the teacher. The applied learning model motivates teachers to be more creative in choosing themes and integrating in Asmaul Husna. The impact of application of the model will show good behavior habits by children in accordance with the 19 indicators of successful achievement model.